Socialization of Digital Marketing Communication Applications in Small Medium Micro Businesses Karawang Regency - Dharta, Firdaus Yuni; Chaerudin, Chaerudin; Ramdani, Danny (Budapest International Research and Critics University, 2022)
Study this expected could give information how far is the perception Public to sell buy digitally based. Result of study this expected could give donation thinking to related parties so that more develop the business again, so that knowledge about business digital -based is very important in this modern and all-round era practical moment this. As for the method approach offered _ for complete problem with object the implementation of SMEs this time is with method education. By short method this is in essence emphasizing knowledge transfer knowledge by direct from expert to Public wide. Event “App Socialization Digital Marketing in MSMEs in Karawang Regency” has done with good. Speakers _ has serve materials needed by the community with the goal is that the community there could use and market the products they have by wider. A number of the obstacles experienced Public like product in need period time for produced, then like a trading mentality is also answered in this event. Product derivative is the key to business future society _ time like production egg Becomes egg more salty _ profitable.